Numerical simulation of co-firing LRC and ammonia in Pangkalan Susu 3 & 4 coal-fired steam power plant (CFSPP) capacity 210 megawatts - I Nyoman Agus Adi Saputra; Teddy Dahlan Manurung; Aditya Eka Yuliadi; Prabowo; Giri Nugroho; Tri Vicca Kusumadewi; Hariana Hariana; Siew Hwa Chan (Case Studies in Thermal Engineering)
The effort to reduce CO2 and NOx emissions plays a crucial role in mitigating climate change, improving air quality, complying with environmental regulations, and promoting clean technology innovation. Ammonia, as an emission-free fuel, shows significant potential as a co-firing agent with Coal in coal-fired steam power plants (CFSPP). Previous studies have demonstrated promising results in emission reduction through ammonia co-firing. This research presents a numerical analysis based on Computational Fluid Dynamics (CFD) to investigate the co-firing of ammonia with low-calorific Coal (LRC) in the CFSPP Pangkalan Susu Units 3 and 4, with a capacity of 210 MW. The study employs fluid flow modelling and chemical reaction analysis using the Discrete Phase Model (DPM) to provide accurate predictions of temperature distribution and pollutant concentrations in pulverized coal boilers. Cofiring simulations were conducted with ammonia additions of 5 % and 15 % on a calorific basis. Injection experiments from each burner (A-D) were performed to identify the optimal injection location. The simulation results indicate changes in combustion characteristics, particularly in temperature distribution. The main finding reveals a temperature decrease when ammonia is added as a co-firing material, attributed to the higher H2O content, which leads to increased moisture losses. In terms of efficiency, co-firing showed a decline compared to the baseline combustion of 100 % LRC coal due to the more significant moisture losses. The highest reduction in CO2 emissions was observed when 15 % ammonia was injected from burner B in case #6, with a mass fraction value of 0.171 at the boiler outlet. Similarly, the most significant reduction in NOx emissions occurred with a 15 % ammonia co-firing from burner B, yielding a mass fraction value of 8.81E-04 at the boiler outlet. This co-firing technology is expected to enhance decarbonization efforts and optimize the use of renewable energy in the future.